Self-reduction copper paste based on thermal decomposition copper salt as well as preparation method and application of self-reduction copper paste

By using self-reducing copper paste based on thermally decomposed copper salt in microelectronic connection technology, nano-copper particles are generated and self-reducing characteristics are used, the problem of poor performance of existing high-temperature solder at high temperatures is solved, and the welding effect with high oxidation resistance and mechanical strength is achieved. It is suitable for electronic packaging and SiC devices.

CN119747963APending Publication Date: 2025-04-04HARBIN INSTITUTE OF TECHNOLOGY (SHENZHEN) (INSTITUTE OF SCIENCE AND TECHNOLOGY INNOVATION HARBIN INSTITUTE OF TECHNOLOGY SHENZHEN)
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411659720.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

It is difficult to achieve excellent thermal properties, mechanical strength, durability and reliability at temperatures above 200°C. In addition, silver sintering has high cost and electrochemical migration problems, while copper sintering requires high temperature treatment and oxidation protection.

Method used

Self-reducing copper paste based on thermal decomposition of copper salt is used. During the sintering process, the paste is thermally decomposed by copper salt to generate nano-copper particles. Combined with self-reducing characteristics, avoiding the addition of reducing agents, simplifying the process, reducing complex chemical reactions, and alleviating oxidation by releasing reducing gases.

Benefits of technology

It achieves the acquisition of dense welded joints under low vacuum conditions, improves oxidation resistance and mechanical strength, extends service life, reduces process complexity and cost, and is suitable for SiC devices under extreme conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747963A_ABST
    Figure CN119747963A_ABST
Patent Text Reader

Abstract

The invention provides self-reduction copper paste based on thermal decomposition copper salt and a preparation method and application thereof.The self-reduction copper paste comprises the thermal decomposition copper salt and an organic solvent, and the thermal decomposition copper salt is at least one of formic acid copper salt, oxalic acid copper salt, copper carbonate, fumaric acid copper salt, squaric acid copper salt, melaic acid copper salt or nicotinic acid copper salt; the organic solvent is one or a mixture of more than two of alpha-terpilenol, ethylene glycol, polyethylene glycol, diethylene glycol, triethylene glycol or propylene glycol. By the adoption of the technical scheme, no reducing agent needs to be additionally added, the nano-copper particles are obtained through thermal decomposition of the copper salt in the sintering process, copper paste sintering connection is achieved through self-reduction, oxidation of the copper particles in the sintering process can be effectively relieved through reducing gas released through decomposition of the copper salt, and formation of a sintering neck is promoted; the quality of a sintered joint is enhanced by reducing the porosity and improving the mechanical strength; and the sintering process is flexible and is suitable for various different manufacturing processes and conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of microelectronic connection technology, and in particular to a self-reducing copper paste based on thermal decomposition copper salt, and a preparation method and application thereof. Background Art

[0002] The development of wide bandgap semiconductor devices has become critical to meet the demand for reliable operation in high temperature environments in fast-growing fields such as electric vehicles, aerospace, and power electronics. Therefore, it is particularly necessary to develop high-temperature interconnect materials that can achieve excellent thermal performance, mechanical strength, durability, and reliability at temperatures above 200°C. In recent years, transient liquid phase bonding (TLP) and silver nanoparticle sintering have become research hotspots for replacing high-temperature solders. Although TLP welding has the advantages of low welding temperature and high operating temperature (250-300°C), its main disadvantage is the formation of voids and brittle intermetallic compounds, which greatly shortens the service life of the solder joints. In contrast, silver sintering has been widely used under pressure, but the high cost of silver is a significant disadvantage. In addition, the phenomenon of silver electrochemical migration is also a major challenge in electronic packaging.

[0003] Copper is a cheaper, abundant and easily accessible material with thermal and mechanical properties similar to those of silver, making copper sintering a promising alternative to silver. However, there is a clear positive correlation between the melting point of bulk materials and the nano-sintering temperature. As a result, copper (melting point is 1083°C) requires a higher sintering temperature than silver (melting point is 962°C). The latest research shows that the sintering temperature of silver is 200-250°C, while the processing temperature of copper sintering is reported to exceed 300°C. In addition, as the temperature increases, the oxidation tendency of copper particles becomes a major challenge. In addition, the problems in the field of copper sintering mainly focus on oxidation protection of copper particles before sintering, sintering in a reducing atmosphere, and the application of redox welding processes. Summary of the invention

[0004] In view of the above technical problems, the present invention discloses a self-reducing copper paste based on thermal decomposition copper salt and a preparation method and application thereof. The copper paste can generate nano copper particles through thermal decomposition of copper salt during the sintering process. Combined with the self-reduction property, the connection quality can be effectively improved. When used in electronic packaging, it has excellent anti-oxidation performance and good mechanical strength, and provides a new solution for improving the reliability of SiC devices under extreme conditions.

[0005] To this end, the technical solution adopted by the present invention is:

[0006] A self-reducing copper paste based on thermally decomposable copper salt, comprising thermally decomposable copper salt and an organic solvent, wherein the thermally decomposable copper salt is at least one of copper formate, copper oxalate, copper carbonate, copper fumarate, copper squarate, copper melanate or copper nicotinate; and the organic solvent is one of α-terpineol, ethylene glycol (EG), polyethylene glycol (PEG), diethylene glycol (DEG), triethylene glycol (TEG) or propylene glycol (PG), or a mixture of two or more thereof.

[0007] The organic solvent can be used as an effective protective agent, which helps to keep the particles finely dispersed and evenly distributed in the copper paste.

[0008] With this technical solution, during the vacuum high-temperature hot-pressing sintering of the self-reducing copper paste, the thermally decomposed copper salt in it thermally decomposes and spontaneously produces reducing copper salts, and nano copper particles can be generated only by heating, without the need for additional reducing agents. This process avoids the reliance on external reducing agents, makes the process simpler and more controllable, and reduces unnecessary complex chemical reactions. Moreover, during the heating process, the thermal decomposition of copper salts will produce reducing gases such as carbon monoxide and hydrogen. The release of these gases can not only alleviate the formation of the oxide layer during the sintering process, but also promote the formation of sintering necks, thereby enhancing the sintering performance of the material. This mechanism provides additional protection for the densification and oxidation resistance of the copper paste.

[0009] As a further improvement of the present invention, the thermally decomposable copper salt includes three copper salts including copper formate. Further, the thermally decomposable copper salt is copper formate, copper melaric acid, and copper nicotinate, and the mass ratio of the three is 2:1:1.

[0010] As a further improvement of the present invention, the particle size of the thermally decomposed copper salt is less than 50 μm.

[0011] As a further improvement of the present invention, the mass ratio of the thermally decomposed copper salt to the organic solvent is 2-10:1.

[0012] As a further improvement of the present invention, the composition of the self-reducing copper paste based on thermal decomposition copper salt also includes an additive, and the additive is one or a mixture of two or more of ethyl cellulose, dimethyl dibutyl alcohol, and carboxymethyl cellulose. With this technical solution, the addition of the additive can improve the interfacial tension between copper particles and the solvent, improve the rheology of the copper paste and enhance its printing performance, and further enhance its stability and operability in industrial applications.

[0013] As a further improvement of the present invention, the mass ratio of the additive to the thermally decomposed copper salt is 1:23-84.

[0014] The present invention also discloses a method for preparing the self-reducing copper paste based on thermal decomposition copper salt as described above, comprising the following steps:

[0015] Step S1, mixing a thermally decomposed copper salt with an organic solvent to obtain a paste A;

[0016] Step S2, mixing the paste A uniformly with a paste mixer to obtain a paste B;

[0017] Step S3, mixing the paste B with an additive to obtain a paste C;

[0018] Step S4, mixing the paste C evenly with a paste mixer to obtain a self-reducing copper paste.

[0019] As a further improvement of the present invention, in step S1, in the paste A, the mass ratio of the thermally decomposed copper salt to the organic solvent is 2 to 10:1.

[0020] As a further improvement of the present invention, in step S1, after the thermally decomposed copper salt is ground, an organic solvent is added for mixing. Further, grinding is performed in a mortar. Further, the particle size of the thermally decomposed copper salt after grinding is less than 50 μm. Using this technical solution, the thermally decomposed copper salt is fully ground, which not only improves the overall performance of the slurry, but also helps to ensure the uniformity of the coating during the printing process. Large-sized crystals may cause uneven coating thickness, thereby affecting the quality of the sintered joint and the performance of the electronic device. Avoid the presence of large-sized crystals in the final copper salt slurry, which affects subsequent printing.

[0021] As a further improvement of the present invention, in step S3, in the paste C, the mass ratio of the paste B to the additive is 20 to 55:1.

[0022] As a further improvement of the present invention, in step S2, the mixing time is 5-60 min; in step S4, the mixing time is 10-120 min.

[0023] The present invention also discloses the use of the self-reducing copper paste based on thermal decomposition copper salt as described above. The self-reducing copper paste is coated on the welding position and subjected to vacuum hot pressing sintering at a temperature not lower than 250°C.

[0024] As a further improvement of the present invention, the sintering temperature is 300-350°C.

[0025] As a further improvement of the present invention, the sintering pressure is 1 to 10 MPa. Further, the sintering pressure is 2 to 10 MPa.

[0026] As a further improvement of the present invention, the vacuum degree is not higher than 5 Pa. This vacuum degree can be achieved by using a common mechanical pump to evacuate without the need for a molecular pump. The copper paste of the technical solution of the present invention can be sintered under low vacuum conditions and a dense welding head can be obtained.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] First, the copper paste of the technical solution of the present invention uses a mixture of copper salts, and no external reducing agent is required. During the sintering process, copper salts are thermally decomposed to obtain nano copper particles, and the copper paste sintering connection is achieved by self-reduction. The reducing gas (H2, CO, etc.) released by the decomposition of copper salts can effectively alleviate the oxidation of copper particles in the sintering process, promote the formation of sintering necks, and enhance the quality of sintered joints by reducing porosity and improving mechanical strength. It can better solve the oxidation problem of copper materials as solder, and has more superior anti-oxidation properties than traditional copper nanoparticles.

[0029] Specifically, the oxidation link can be divided into oxidation during storage and oxidation during sintering. In the storage link, the copper metal salt in the copper paste of the technical solution of the present invention will not react with oxygen, which solves the oxidation of the copper paste during storage, which means that during long-term storage, the slurry can resist oxidation, thereby ensuring the stability and service life of the material. This is crucial for the electronic packaging industry because the stability and reliability of the material directly affect the quality and performance of the final product. In the sintering link, compared with the traditional nano-copper particle sintering process, a reducing atmosphere is required to protect the sintering process. The copper paste of the technical solution of the present invention has a self-reducing property, which can release a reducing atmosphere through thermal decomposition, reduce the copper oxide generated due to high temperature, and ensure the stable growth of the sintering neck. This feature enables the slurry to achieve dense sintering under low vacuum conditions (less than 5Pa), reducing the requirements for the sintering environment. This not only improves the flexibility of the process, but also makes the slurry more suitable for a variety of different manufacturing processes and conditions, expanding its scope of application.

[0030] Second, the thermally decomposed copper salt used in the technical solution of the present invention can form fine nano copper particles with a diameter of less than 10nm by in-situ decomposition during sintering. Compared with chemically synthesized nano copper particles (usually >50nm), it has a better surface energy advantage. The generation of these nano copper particles significantly improves the sintering performance and enhances the mechanical strength of the solder joint. These excellent properties make the new copper paste have great application value in electronic packaging, especially in environments requiring high reliability and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the cross-sectional morphology of the copper paste sintered solder joint in Example 1 of the present invention.

[0032] Figure 2 This is the cross-sectional morphology of the copper paste sintered solder joint in Example 2 of the present invention.

[0033] Figure 3 This is the cross-sectional morphology of the copper paste sintered solder joint in Example 3 of the present invention.

[0034] Figure 4 This is the cross-sectional morphology of the copper paste sintered solder joint in Example 4 of the present invention.

[0035] Figure 5 This is the cross-sectional morphology of the copper paste sintered solder joint in Example 5 of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0037] Example 1

[0038] A self-reducing copper paste based on thermal decomposition copper salt, the specific steps of the preparation method thereof are:

[0039] Step S1, copper formate, copper oxalate, and copper carbonate are mixed in a mass ratio of 1:1:1, the thermally decomposed metal salt is fully ground in a mortar, and α-terpineol, EG, and PEG mixed in a mass ratio of 1:1:1 are added so that the mass ratio of the decomposed Cu salt to the organic solvent is 3:1, to obtain a paste A;

[0040] Step S2, the paste A in step S1 is uniformly mixed in a paste mixer for 60 minutes to obtain a paste B;

[0041] Step S3, adding carboxymethyl cellulose to the paste B mixed in step S2, wherein the mass ratio of the paste B to the carboxymethyl cellulose is 20:1, to obtain a paste C.

[0042] Step S4, the paste C in step S3 is uniformly mixed in a paste mixer for 100 minutes to obtain a copper paste.

[0043] The copper paste was used to print on the surface of the copper-clad ceramic substrate using a steel screen, and the copper sheet on top was hot-pressed and sintered for 20 minutes at 250°C and 3Pa vacuum under a pressure of 1MPa. The cross-sectional morphology of the sintered solder joint obtained in this example is as follows: Figure 1 As shown, it can be seen that there is obvious copper particle sintering in the solder joint, but due to the low pressure, there are still obvious holes in the solder joint.

[0044] Example 2

[0045] A self-reducing copper paste based on thermal decomposition copper salt, the specific steps of its preparation are:

[0046] Step S1, copper formate, copper fumarate, and copper squarate are mixed in a mass ratio of 2:1:1, the thermally decomposed metal salt is fully ground in a mortar, and TEG, DEG, and PEG mixed in a mass ratio of 1:1:1 are added so that the mass ratio of the decomposed Cu salt to the organic solvent is 3:1, to obtain a paste A;

[0047] Step S2, the paste A in step S1 is uniformly mixed in a paste mixer for 60 minutes to obtain a paste B;

[0048] Step S3, adding ethyl cellulose to the paste B mixed in step S2, wherein the mass ratio of the paste B to the ethyl cellulose is 30:1, to obtain a paste C.

[0049] Step S4, the paste C in step S3 is uniformly mixed in a paste mixer for 100 minutes to obtain a copper paste.

[0050] The copper paste was used to print on the surface of the copper-clad ceramic substrate using a steel screen, and the copper sheet on top was hot-pressed and sintered for 20 minutes at 300°C and 4Pa vacuum under a pressure of 1MPa. The cross-sectional morphology of the sintered solder joint obtained in this example is as follows: Figure 2 As shown, it can be seen that the holes in the solder joints have disappeared. At the same time, due to the diffusion of atoms at the particle interface, the sintering neck between the particles has increased significantly, the contact area has increased, and the bonding strength has increased.

[0051] Example 3

[0052] A self-reducing copper paste based on thermal decomposition copper salt, the specific steps of its preparation are:

[0053] Step S1, copper formate, copper melaric acid, and copper nicotinate are mixed in a mass ratio of 2:1:1, the thermally decomposed metal salt is fully ground in a mortar, and EG, PG, and PEG mixed in a mass ratio of 1:1:1 are added so that the mass ratio of the decomposed Cu salt to the organic solvent is 2.8:1, to obtain a paste A;

[0054] Step S2, the paste A in step S1 is uniformly mixed in a paste mixer for 60 minutes to obtain a paste B;

[0055] Step S3, adding dimethyl dibutyl alcohol to the paste B mixed in step S2, wherein the mass ratio of paste B to dimethyl dibutyl alcohol is 20:1, to obtain paste C.

[0056] Step S4, the paste C in step S3 is uniformly mixed in a paste mixer for 100 minutes to obtain a copper paste.

[0057] The copper paste was used to print on the surface of the copper-clad ceramic substrate using a steel screen, and the copper sheet on top was sintered at 300°C under a pressure of 2MPa for 20 minutes. The cross-sectional morphology of the sintered solder joint obtained in this example is as follows: Figure 3 As shown, it can be seen that the spherical structure of the copper particles in the solder joint has almost disappeared, the solder joint after sintering is relatively dense, and the porosity decreases, accompanied by the growth of the sintering neck to reach a steady state.

[0058] Example 4

[0059] A self-reducing copper paste based on thermal decomposition copper salt, the specific steps of its preparation are:

[0060] Step S1, copper formate, copper melaric acid, and copper nicotinate are mixed in a mass ratio of 1:1:1, the thermally decomposed metal salt is fully ground in a mortar, and EG, PG, and PEG mixed in a mass ratio of 1:2:1 are added so that the mass ratio of the decomposed Cu salt to the organic solvent is 3.2:1, to obtain a paste A;

[0061] Step S2, the paste A in step S1 is uniformly mixed in a paste mixer for 60 minutes to obtain a paste B;

[0062] Step S3, adding dimethyl dibutyl alcohol to the paste B mixed in step S2, wherein the mass ratio of paste B to dimethyl dibutyl alcohol is 20:1, to obtain paste C.

[0063] Step S4, the paste C in step S3 is uniformly mixed in a paste mixer for 100 minutes to obtain a copper paste.

[0064] The copper paste was used to print on the surface of the copper-clad ceramic substrate using a steel screen, and the copper sheet on top was hot-pressed and sintered for 20 minutes at 300°C and 5Pa vacuum under a pressure of 2MPa. The cross-sectional morphology of the sintered solder joint obtained in this example is as follows: Figure 4 As shown, it can be seen that under a lower vacuum degree, the sintering of copper particles is not significantly affected, and a continuous and complete copper skeleton structure is still formed.

[0065] Example 5

[0066] A self-reducing copper paste based on thermal decomposition copper salt, the specific steps of its preparation are:

[0067] Step S1, copper formate, copper oxalate, and copper carbonate are mixed in a mass ratio of 1:1:1, the thermally decomposed metal salt is fully ground in a mortar, and α-terpineol, EG, and PEG mixed in a mass ratio of 1:1:1 are added so that the mass ratio of the decomposed Cu salt to the organic solvent is 3:1, to obtain a paste A;

[0068] Step S2, the paste A in step S1 is uniformly mixed in a paste mixer for 60 minutes to obtain a paste B;

[0069] Step S3, adding ethyl cellulose to the paste B mixed in step S2, wherein the mass ratio of the paste B to the ethyl cellulose is 20:1, to obtain a paste C.

[0070] Step S4, the paste C in step S3 is uniformly mixed in a paste mixer for 100 minutes to obtain a copper paste.

[0071] The copper paste was used to print on the surface of the copper-clad ceramic substrate using a steel screen, and the copper sheet was covered on top and sintered at 350°C under a pressure of 10 MPa for 60 minutes. The cross-sectional morphology of the sintered solder joint obtained in this example is as follows: Figure 5 As shown, it can be seen that after sintering and bonding at high temperature, high vacuum and for a long time, there are almost no pores in the solder joint, forming a compact and dense block structure.

[0072] Based on the comparison of the above examples 1-5, it can be found that the thermal decomposition type copper salt has excellent sinterability. During the sintering process, as the temperature and time increase, the thermal decomposition of the copper salt not only generates nano-scale copper particles, but also releases a reducing atmosphere, which effectively inhibits the formation of copper oxide and avoids the defect of the traditional copper paste being easily oxidized at high temperatures. At the same time, this reducing environment promotes the growth of the sintering neck, making the sintered body of the solder joint cross section more compact, thereby improving the strength and reliability of welding.

[0073] In addition, with the further increase of sintering temperature, sintering pressure and sintering time, the porosity of the solder joint is significantly reduced. This reduction in porosity not only improves the mechanical properties of the solder joint, but also improves its fatigue resistance and durability. By adjusting the sintering conditions, the microstructure of the solder joint can be optimized to achieve the best performance. This feature makes thermal decomposition copper salts show great flexibility and adaptability in practical applications, providing new solutions for electronic packaging and other related fields.

[0074] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the protection scope of the present invention.

Claims

1. A self-reducing copper paste based on thermal decomposition copper salt, characterized in that: Its components include thermally decomposable copper salt and organic solvent, wherein the thermally decomposable copper salt is at least one of copper formate, copper oxalate, copper carbonate, copper fumarate, copper squarate, copper melanate or copper nicotinate; and the organic solvent is one of α-terpineol, ethylene glycol, polyethylene glycol, diethylene glycol, triethylene glycol or propylene glycol, or a mixture of two or more thereof.

2. The self-reducing copper paste based on thermal decomposition copper salt according to claim 1, characterized in that: The mass ratio of the thermally decomposed copper salt to the organic solvent is 2-10:

1.

3. The self-reducing copper paste based on thermal decomposition copper salt according to claim 2, characterized in that: The composition also includes additives, which are one or a mixture of two or more of ethyl cellulose, dimethyl dibutyl alcohol and carboxymethyl cellulose.

4. The self-reducing copper paste based on thermal decomposition copper salt according to claim 3, characterized in that: The mass ratio of the additive to the thermally decomposed copper salt is 1:23-84.

5. The method for preparing a self-reducing copper paste based on thermal decomposition copper salt according to claim 3 or 4, characterized in that: The steps include: Step S1, mixing a thermally decomposed copper salt with an organic solvent to obtain a paste A; Step S2, mixing the paste A uniformly with a paste mixer to obtain a paste B; Step S3, mixing the paste B with an additive to obtain a paste C; Step S4, mixing the paste C evenly with a paste mixer to obtain a self-reducing copper paste.

6. The self-reducing copper paste based on thermal decomposition copper salt according to claim 5, characterized in that: In step S1, in the paste A, the mass ratio of the thermally decomposed copper salt to the organic solvent is 2-10:1; in step S3, in the paste C, the mass ratio of the paste B to the additive is 20-55:

1.

7. The self-reducing copper paste based on thermally decomposed copper salt according to claim 6, characterized in that: In step S1, the thermally decomposed copper salt is ground and then an organic solvent is added for mixing.

8. The self-reducing copper paste based on thermally decomposed copper salt according to claim 5, characterized in that: In step S2, the mixing time is 5-60 min; in step S4, the mixing time is 10-120 min.

9. The use of the self-reducing copper paste based on thermal decomposition copper salt according to any one of claims 1 to 4, characterized in that: The self-reducing copper paste is coated on the part to be welded and subjected to vacuum hot pressing sintering, with the sintering temperature being not less than 250°C.

10. The use of the self-reducing copper paste based on thermal decomposition copper salt according to claim 9, characterized in that: The sintering temperature is 300-350° C., the pressure is 1-10 MPa, and the vacuum degree is not greater than 5 Pa.

Citation Information

Patent Citations

  • Low-temperature sintered nano-copper soldering paste, and preparation method and application method of low-temperature sintered nano-copper soldering paste

    CN114643435A

  • Low-temperature sintered high-strength copper paste as well as preparation method and application thereof

    CN118969358A

  • Copper composite particle, copper paste comprising the same and method of producing circuit board using the same

    JP2015030869A

  • Composite particle, copper paste composition and method for producing the same, and conductor

    JP2017095780A

  • Coated copper particles and method for producing the same

    US20170043404A1